1993
DOI: 10.1099/00221287-139-4-847
|View full text |Cite
|
Sign up to set email alerts
|

Gradients in the expression of cell surface glycoproteins in a simple tissue, the Dictyostelium discoideum slug

Abstract: Gradients in diffusible morphogens have long been postulated to have a role in the establishment of polarity and pattern formation in developing animal embryos. In the cellular slime mould Dictyostelium discoideum, several morphogens have been described and their interactions and location in the multicellular 'slug' stage are being studied. Here we report that two cell surface antigens, which identify prespore and prestalk cells, respectively, are present at different levels on the surface of cells depending o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Browne and Williams (1993) have shown that PsA is unevenly distributed within the slug, prespore cells at the posterior end of the slug having greater levels of PsA than those in the anterior. Transcription of the pspA gene, which encodes PsA, is CAMP-dependent (Barklis and Lodish, 1983), which suggests the possible presence of morphogenetic gradients of CAMP within the slug (Browne and Williams, 1993).…”
mentioning
confidence: 98%
“…Browne and Williams (1993) have shown that PsA is unevenly distributed within the slug, prespore cells at the posterior end of the slug having greater levels of PsA than those in the anterior. Transcription of the pspA gene, which encodes PsA, is CAMP-dependent (Barklis and Lodish, 1983), which suggests the possible presence of morphogenetic gradients of CAMP within the slug (Browne and Williams, 1993).…”
mentioning
confidence: 98%
“…This glycoprotein is the predominant cell surface protein during slug phase of the D. discoideum life cycle, and the molecule's emergence on the cell surface signals the initiation of organized multicellular tissue (11). There has recently been a substantial increase in structural information concerning proteins involved in cell adhesion, with several types of three-dimensional folds now defined from among the clearly identifiable and recurring protein modules (12)(13)(14). It remains to be seen where PsA fits within the existing classes of cell surface molecular structures.…”
mentioning
confidence: 99%
“…A model system in which these cellular processes has been particularly well studied is the eukaryote Dictyostelium discoideum (Coates and Harwood 2001). This report concerns pre-spore specific antigen (PsA), the most abundant cell surface protein of D. discoideum in the multicellular stage of its life cycle, where it occurs spread in a spatial gradient across the slug tissue (Browne and Williams 1993).…”
mentioning
confidence: 99%